Does Stake Size matter for Cooperation and Punishment? - Martin G. Kocher; Peter Martinsson; Martine Visser (Tinbergen Institute, 2006)
The effects of stake size on cooperation and punishment are investigated using a public goods experiment. We find that an increase in stake size does neither significantly affect cooperation nor, interestingly, the level of punishment.
Keywords: C72; C91; H41; 330; experiment; public goods; punishment; stake size